Effect of Annealing Temperature on CuInSe2/ZnS Thin-Film Solar Cells Fabricated by Using Electron Beam Evaporation - H. Abdullah; S. Habibi (International Journal of Photoenergy)
CuInSe2 (CIS) thin films are successfully prepared by electron beam evaporation. Pure Cu, In, and Se powders were mixed and ground in a grinder and made into a pellet. The pallets were deposited via electron beam evaporation on FTO substrates and were varied by varying the annealing temperatures, at room temperature, 250°C, 300°C, and 350°C. Samples were analysed by X-ray diffractometry (XRD) for crystallinity and field-emission scanning electron microscopy (FESEM) for grain size and thickness. I-V measurements were used to measure the efficiency of the CuInSe2/ZnS solar cells. XRD results show that the crystallinity of the films improved as the temperature was increased. The temperature dependence of crystallinity indicates polycrystalline behaviour in the CuInSe2 films with (1 1 1), (2 2 0)/(2 0 4), and (3 1 2)/(1 1 6) planes at 27°, 45°, and 53°, respectively. FESEM images show the homogeneity of the CuInSe2 formed. I-V measurements indicated that higher annealing temperatures increase the efficiency of CuInSe2 solar cells from approximately 0.99% for the as-deposited films to 1.12% for the annealed films. Hence, we can conclude that the overall cell performance is strongly dependent on the annealing temperature.